Healthy aging in Asia - Eggleston, Karen; Walter H. Shorenstein Asia-Pacific Research Center (Stanford, CA : The Walter H. Shorenstein Asia-Pacific Research Center, Freeman Spogli Institute for International Studies, Stanford University, 2020)
Life expectancy in Japan, South Korea, and much of urban China has now outpaced that of the United States and other high-income countries. With this triumph of longevity, however, comes a rise in the burden of noncommunicable diseases (NCDs) like diabetes and hypertension, reducing healthy life years for individuals in these aging populations, as well as challenging the healthcare systems they rely on for appropriate care. The challenges and disparities are even more pressing in low- and middle-income economies, such as rural China and India. Moreover, the COVID-19 pandemic has underscored the vulnerability to newly emerging pathogens of older adults suffering from NCDs, and the importance of building long-term, resilient health systems. What strategies have been tried to prevent NCDs--the primary cause of morbidity and mortality -- as well as to screen for early detection, raise the quality of care, improve medication adherence, reduce unnecessary hospitalizations and increase "value for money" in health spending? Fourteen concise chapters cover multiple aspects of policy initiatives for healthy aging and economic research on chronic disease control in diverse health systems -- from cities such as Singapore and Hong Kong to large economies such as Japan, India, and China.
Healthy Aging in Asia: Introduction / Karen Eggleston -- Healthy Aging and Inequality in Age of Death: Comparing Trends in Japan, Korea, Singapore, and the United States / Karen Eggleston, Victor R. Fuchs, Daejung Kim, and Zhi Ping Teo -- Healthy Aging and Economic Research on the Net Value of Noncommunicable Disease Management in Japan / Chiyo Hashimoto and Karen Eggleston -- The Political Economy of Precision Health: The Case of Japan / Minori Ito -- Personalized and Precision Medicine in Japan / Hokuto Asano -- Diabetes Care Management and Policy toward Healthy Aging in South Korea / Hongsoo Kim -- Noncommunicable Disease Management in Hong Kong: Current Policies and the Potential Role of Economics Research / Janet Tin Kei Lam, Sabrina Wong, and Jianchao Quan -- Creating National Demonstration Areas for the Integrated Prevention and Control of Noncommunicable Diseases in China / Jianqun Dong, Fan Mao, Wenlan Dong, Yingying Jiang, Shiwei Liu, and Maigeng Zhou -- Avoidable Admission Rates for Diabetes Patients and Associated Medical Spending in Rural China: Evidence from Zhejiang Province / Min Yu, Yiwei Chen, Hui Ding, Jieming Zhong, Ruying Hu, Chunmei Wang, Kaixu Xie, Xiangyu Chen, Haibin Wu, Pedro Gallardo, and Karen Eggleston -- Exploring and Promoting the Family Doctor System in an Aging China / Rize Jing and Hai Fang -- Hypertension Control after Health Insurance Expansion: Empirical Evidence from China / Jason Li -- Private Roles for Public Goals in China's Social Services / Jack Donahue, Karen Eggleston, Yijia Jing, and Richard J. Zeckhauser -- Cancer, Disparities, and Public-Private Roles / Karen Eggleston, Jui-fen Rachel Lu, Christina Ping, and Nancy Zhang -- Healthy Aging Policies in India / Kavita Singh and Dorairaj Prabhakaran -- Appendix: Methods for Estimating Net Value of Chronic Disease Management.
Includes bibliographical references and index.
Keywords: Health services for the aged; Chronic disease -- Economics; Health policy